Carbohydrate Contents of Some Insecticidal Compositae Plants - Saxena, V.K.; Basedia, G.M. (Asian Journal of Chemistry, 2010)
The present communication describes the results of chromatographic analysis for sugars from the leaves of Artemisia vulgaris and the stems of Matricaria chamomilla. The sugars were identified by paper chromatography with the help of authentic samples of sugars.